A zero-valent iron-manganese bionic coral island and its preparation method and application
The zero-valent iron-manganese bimetallic nanorod array wrapped with graphitized carbon film was prepared by one-step carbon thermal reduction method, forming a bionic coral island structure, solving the problems of limited dehalogenation capacity of zero-valent iron and complex preparation method, and achieving efficient degradation of halogen The effect of replacing organic pollutants.
Patent Information
- Application Number
- CN202411679281.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-22
AI Technical Summary
In the prior art, the dehalogenation capacity of zero-valent iron is limited, active nano zero-valent iron is prone to self-ignition and passivation, and the preparation method for preparing zero-valent iron-manganese bimetallic materials is complicated.
By mixing zinc chloride, ferric chloride, manganese dichloride and biomass raw materials in water, forming a precursor and pyrolyzed under an inert atmosphere, a one-step carbon thermal reduction method was used to prepare a graphitized carbon film wrapped in a graphitized carbon film. Zero-valent iron-manganese bimetallic nanorod array forms a bionic coral island structure.
The reduction and dehalogenation capacity of zero-valent iron is strengthened, the catalytic H2O2 performance is improved, and the efficient degradation of organic pollutants is achieved, especially the difficult-to-degrade halogenated organic pollutants, and the material stability is improved.
Smart Images

Figure CN119175102B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of environmental functional materials, and more specifically, to a zero-valent iron-manganese bionic coral island and a preparation method and application thereof. Background Art
[0002] With the rapid development of global industry, halogenated organic compounds are mass-produced and widely used as industrial raw materials, reagents or products. However, halogenated organic compounds are toxic and harmful, and have stable physical and chemical properties and are not easily degraded. As a result, they exist in large quantities in industrial wastewater, groundwater and soil of industrial sites, and are frequently detected, which seriously threatens human and ecological health and has attracted great attention.
[0003] At present, there are many reports on the degradation and removal technologies of halogenated organic pollutants, such as advanced oxidation and zero-valent iron reduction. Among them, the most widely used advanced oxidation is the Fenton method. The Fenton method is Fe 2+ At pH = 2.5 ~ 3.5, hydrogen peroxide is catalyzed to produce highly active hydroxyl radicals and other reactive oxygen species. These reactive oxygen species can effectively degrade those highly stable and difficult to degrade organic pollutants, thereby achieving deep oxidation and maximizing the removal of organic pollutants. Although the Fenton method has a good oxidative degradation effect on most organic compounds, the degradation efficiency of halogenated organic pollutants is greatly reduced due to the strong electron-withdrawing property of halogens in halogenated organic matter. The chemical reduction method has a good dehalogenation effect, but the reduction reaction often has a low rate and does not completely degrade halogenated organic pollutants. It is also easy to produce toxic intermediates. Therefore, the dehalogenation reduction intermediates need to be further degraded to avoid the risk of reduction treatment.
[0004] Zero-valent iron is an active metal with abundant sources and low price. Its standard electrode potential is E°(Fe 2+ / Fe) = -0.440 V, showing strong reducing ability. Nano zero-valent iron has small particle size, high surface activity, and strong reducing ability. It can directly reduce chloroaromatic hydrocarbons and other difficult-to-degrade organic pollutants. The dissolved Fe 2+It can also form a Fenton advanced oxidation system with hydrogen peroxide, thereby quickly oxidizing or even mineralizing difficult-to-degrade organic pollutants. Many studies have shown that nano zero-valent iron has a strong ability to reduce and dehalogenate, including reducing and degrading halogenated organic pollutants such as chlorinated alkanes, organochlorine pesticides, and chlorophenols. On the one hand, it can reduce the halogen atoms on halogen-containing organic pollutants and greatly reduce the biological toxicity of pollutants. On the other hand, it can reduce the chemical stability of pollutants, making them more easily oxidized and degraded into small molecules or even completely mineralized. However, zero-valent iron has limited dehalogenation ability during its application, and the active surface of nano zero-valent iron is easily oxidized or even self-ignited, forming an oxide film, which hinders electron mass transfer. There are many studies in the prior art on the modification of zero-valent iron. Among them, manganese metal doping to prepare zero-valent iron-manganese bimetallic materials is a good method. For example, in Chinese patent application CN111804930A, a two-step liquid phase reduction is used to prepare a zero-valent iron-manganese bimetallic. However, the preparation method requires the use of expensive sodium borohydride for reduction, and the preparation process is complicated. In addition, the prepared zero-valent iron-manganese bimetallic is exposed to the outside and is easily interfered by other impurities during application, thereby being inactivated.
[0005] Therefore, it is still a great challenge to prepare zero-valent iron-based materials that have both strong reducing ability and good stability. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art, such as the limited dehalogenation capacity of zero-valent iron, the easy spontaneous combustion and passivation of active nano zero-valent iron, and the complex preparation method of metal-doped zero-valent iron, and to provide a preparation method of a zero-valent iron-manganese bionic coral island.
[0007] The purpose of the present invention is to provide a zero-valent iron-manganese bionic coral island.
[0008] Another object of the present invention is to provide the application of the zero-valent iron manganese bionic coral island in degrading organic pollutants.
[0009] The above-mentioned purpose of the present invention is achieved through the following solutions:
[0010] The present invention provides a method for preparing a zero-valent iron-manganese bionic coral island, comprising the following steps:
[0011] S1. Mixing zinc chloride, ferric chloride, manganese dichloride and biomass raw materials in water to obtain a precursor;
[0012] S2. The precursor described in S1 is pyrolyzed at 870-950° C. under an inert atmosphere, and post-treated to obtain a zero-valent iron-manganese bionic coral island;
[0013] Wherein, the molar ratio of ferric chloride to manganese dichloride is 1: (0.8-1.1).
[0014] The zero-valent iron-manganese bionic coral island of the present invention uses biomass raw materials as carbon precursors, adopts zinc chloride as the main pore-forming agent, and adds ferric chloride and manganese chloride as auxiliary pore-forming agents to prepare an iron-manganese precursor, which is then prepared by a one-step carbon thermal reduction method under an inert atmosphere.
[0015] The zero-valent iron-manganese bionic coral island prepared by the present invention strengthens the reduction and dehalogenation ability of zero-valent iron by forming an iron-manganese alloy, and the dissolved Mn 2+ , Mn 3+ It not only has Fenton-like catalytic activity, but also can accelerate the Fe 3+ Fe 2+ In the zero-valent iron-manganese bionic coral island prepared by the present invention, a zero-valent iron-manganese bimetallic nanorod array wrapped with a layer of carbon film grows uniformly on the porous biocarbon surface, shaped like a coral island, and just like corals preying on plankton, the iron-manganese nanorods wrapped with a layer of carbon film can adsorb and capture organic pollutants in the water. At the same time, the zero-valent iron-manganese bionic coral island exerts excellent H2O2 catalytic performance to achieve efficient degradation of organic pollutants.
[0016] In the prior art, carbon thermal reduction alone can produce zero-valent iron, but cannot produce zero-valent manganese, and zero-valent manganese often needs to be prepared by expensive sodium borohydride reduction. However, the inventors have found through a large number of experimental studies that when the molar ratio of ferric chloride to manganese dichloride is in the range of 1: (0.8~1.1), a zero-valent iron-manganese alloy can be formed by a one-step carbon thermal reduction method. Zero-valent manganese has a standard reduction potential of -1.18V, which has a stronger reducing ability than zero-valent iron, and the dissolved Mn 2+ , Mn 3+ It not only has Fenton-like catalytic activity, but also can accelerate the Fe 3+ Fe 2+ In addition, manganese is a graphitized catalyst, which can promote the coating of graphitized carbon film on the surface of zero-valent iron-manganese alloy. The carbon film can protect zero-valent iron-manganese from interference by many substrates in water, such as NOM and anions, and improve its stability. At the same time, the graphitized carbon film can also promote the transmission of electrons in the degradation reaction of organic pollutants. If the proportion of manganese dichloride is too low, the bionic coral island structure of zero-valent iron-manganese nanorods coated with highly graphitized carbon film cannot be formed, reducing the catalytic activity; and if the proportion of manganese dioxide is too high, it will cause metal agglomeration, and this special coral island structure cannot be formed after agglomeration, which will lead to a decrease in activity.
[0017] In the present invention, zinc chloride is used as the main pore-forming agent, which can be completely volatilized during the reaction process and will not affect the catalytic effect of the final material.
[0018] In the present invention, the pyrolysis temperature is 870-950°C. If the pyrolysis temperature is too low, it is not conducive to pore formation, carbon graphitization and carbon thermal reduction reaction, and the bionic coral island structure of zero-valent iron manganese nanorods coated with highly graphitized carbon film cannot be formed, thereby reducing the catalytic activity. If the pyrolysis temperature is too high, the iron and manganese species are prone to agglomeration, and the pore structure in the carrier biochar is prone to collapse, and the bionic coral island structure of zero-valent iron manganese nanorods coated with highly graphitized carbon film cannot be formed, thereby reducing the catalytic activity.
[0019] Preferably, the pyrolysis temperature is 870-900° C. The zero-valent iron-manganese bionic coral island prepared within this temperature range has better catalytic degradation ability of halogenated organic pollutants.
[0020] Preferably, the molar ratio of ferric chloride to manganese dichloride is 1:(0.9-1.1). Specifically, the molar ratio of ferric chloride to manganese dichloride is any one of 1:0.9, 1:0.95, 1:1, 1:1.1, or an interval formed by any of the above ratios, such as 1:(0.9-0.95), 1:(0.9-1), 1:(0.95-1.1), etc., but the present invention is not limited thereto.
[0021] Preferably, the mass ratio of the biomass raw material to zinc chloride is 1: (0.8-1.2). When the mass ratio of the biomass raw material to zinc chloride of the present invention is within the above range, the iron-manganese nanorods are more likely to attach to the surface of the biomass and grow into zero-valent iron-manganese bionic coral islands, and the prepared zero-valent iron-manganese bionic coral islands have better ability to adsorb and enrich organic pollutants and better catalytic activity.
[0022] More preferably, the mass ratio of the biomass raw material to zinc chloride is 1:1.
[0023] Preferably, the mass ratio of the biomass raw material to ferric chloride is 1:(0.4-0.6). When the mass ratio of the biomass raw material to ferric chloride of the present invention is within the above range, the prepared zero-valent iron-manganese bionic coral island can better adsorb and enrich organic pollutants and has better catalytic activity.
[0024] More preferably, the mass ratio of the biomass raw material to ferric chloride is 1:(0.4-0.5).
[0025] Preferably, the concentration of the biomass raw material in the precursor is 0.3-0.4 g / mL.
[0026] Preferably, the heating rate of the pyrolysis is 3-8°C / min. Within this heating rate range, the carbon carrier gradually forms a stable porous structure, and the zero-valent iron manganese nanorods gradually self-assemble and arrange in an orderly manner, which is more conducive to forming a bionic coral island structure of zero-valent iron manganese nanorods.
[0027] More preferably, the heating rate of the pyrolysis is 5-6 °C / min.
[0028] Preferably, the pyrolysis time is 1.5 to 3 h. Within this range, the zero-valent iron-manganese bionic coral island prepared by pyrolysis has better catalytic performance.
[0029] Preferably, the pyrolysis time is 2 to 3 h.
[0030] More preferably, the pyrolysis time is 1.9 to 2.1 h.
[0031] Preferably, the biomass raw material is one or more of straw, wheat bran, rice husk, leaves or bean dregs.
[0032] Preferably, the inert atmosphere is nitrogen or argon. More preferably, the inert atmosphere is nitrogen.
[0033] Preferably, the post-treatment is cooling to room temperature.
[0034] The zero-valent iron-manganese bionic coral island prepared by the present invention can be stored in a vacuum desiccator for future use.
[0035] At the same time, the present invention also protects the zero-valent iron-manganese bionic coral island prepared by the preparation method.
[0036] Additionally, the present invention protects the use of the zero-valent iron manganese bionic coral island in degrading organic pollutants.
[0037] The zero-valent iron manganese bionic coral island of the present invention has good Fenton-like catalytic activity and can catalytically degrade organic pollutants. In addition, the generation of zero-valent manganese can promote the reduction and dehalogenation of zero-valent iron, and has a good removal ability for halogenated organic pollutants that are difficult to degrade in organic pollutants. The graphitized carbon film coated on the surface of the zero-valent iron manganese alloy can also adsorb and capture halogenated organic pollutants, thereby triggering the transfer of electrons from the zero-valent iron manganese to the captured halogenated organic pollutants to achieve reduction and dehalogenation. At the same time, the zero-valent iron manganese bionic coral island also has excellent catalytic H2O2 performance, combining reduction and dehalogenation with catalytic oxidation functions, and ultimately can achieve efficient degradation of halogenated organic pollutants in water.
[0038] Preferably, the organic pollutants are organic substances that are difficult to degrade, including but not limited to halogenated organic pollutants.
[0039] More preferably, the halogenated organic pollutants are fluorinated organic pollutants, chlorinated organic pollutants and brominated organic pollutants.
[0040] The zero-valent iron manganese bionic coral island of the present invention can be used as a hydrogen peroxide catalyst to catalyze H2O2 (Fenton-like oxidation reaction) to degrade halogenated organic pollutants in industrial wastewater, groundwater or soil. The zero-valent iron manganese bionic coral island prepared by the present invention catalyzes the Fenton-like reaction and can effectively degrade halogenated organic pollutants, with a removal rate of at least 83.6% for 2,4,6-trichlorophenol.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The zero-valent iron-manganese bionic coral island of the present invention forms a zero-valent iron-manganese alloy by a simple one-step carbon thermal method. The zero-valent manganese has a standard reduction potential of -1.18V and has a stronger reduction ability than zero-valent iron. By forming an iron-manganese alloy, the reduction and dehalogenation ability of zero-valent iron is enhanced, which is beneficial to the degradation of halogenated organic pollutants, and the dissolved Mn 2+ , Mn 3+ It not only has Fenton-like catalytic activity, but also can accelerate the Fe 3+ Fe 2+ conversion efficiency. The zero-valent iron-manganese bionic coral island described in the present invention is a zero-valent iron-manganese bimetallic nanorod array wrapped with a layer of graphitized carbon film, which grows uniformly on the porous biocarbon surface and is shaped like a coral island. Just like corals preying on plankton, the iron-manganese nanorods wrapped with a layer of graphitized carbon film can adsorb and capture hydrophobic halogenated organic pollutants in the water, thereby triggering the transfer of electrons from the zero-valent iron-manganese to the captured halogenated organic pollutants to achieve reduction and dehalogenation. The graphitized carbon film can also promote electron transmission in the degradation reaction of organic pollutants; at the same time, the carbon film can also protect the zero-valent iron-manganese from being interfered by many matrices in the water, such as NOM, anions, etc., thereby improving the stability of the material. The zero-valent iron-manganese bionic coral island prepared by the present invention has excellent H2O2 catalytic performance and reduction and dehalogenation ability, so that it has a good degradation effect on organic pollutants, especially difficult-to-degrade halogenated organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 1 and 2 are XRD diagrams of the products prepared in Example 1, Comparative Example 1 and Comparative Example 2, wherein FeMn@BC is the product prepared in Example 1, and Fe@BC and Mn@BC are the products prepared in Comparative Examples 1 and 2, respectively.
[0044] Figure 2 The scanning electron microscope image and element distribution map of the product prepared in Example 1 are shown in FIG. Figure 2 The left picture in the figure is a scanning electron microscope image of the final product, zero-valent iron manganese bionic coral island (FeMn@BC), prepared in Example 1, and a schematic diagram of an actual coral island; Figure 2 The right picture in the figure is the element distribution map of the final product zero-valent iron manganese bionic coral island (FeMn@BC) prepared in Example 1. DETAILED DESCRIPTION
[0045] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0046] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0047] Example 1
[0048] A zero-valent iron-manganese bionic coral island, the preparation process is as follows:
[0049] S1. Dissolve 5.0 g FeCl3, 6.2 g MnCl2·4H2O and 10.0 g ZnCl2 completely in 30 mL pure water, add 10.0 g dregs powder, and stir thoroughly until a paste is formed to obtain the precursor;
[0050] S2. The precursor of S1 was placed in a tubular furnace, and under the protection of argon, the temperature was raised to 900°C at a rate of 5°C / min, and pyrolyzed at 900°C for 2 h. After cooling to room temperature, a zero-valent iron-manganese bionic coral island was obtained.
[0051] Example 2
[0052] A zero-valent iron-manganese bionic coral island, the preparation process is as follows:
[0053] S1. Dissolve 5.0 g FeCl3, 6.2 g MnCl2·4H2O and 10.0 g ZnCl2 completely in 30 mL pure water, add 10.0 g dregs powder, and stir thoroughly until a paste is formed to obtain the precursor;
[0054] S2. The precursor of S1 was placed in a tubular furnace, and under argon protection, the temperature was raised to 870°C at a rate of 5°C / min, and pyrolyzed at 870°C for 3 h. After cooling to room temperature, a zero-valent iron-manganese bionic coral island was obtained.
[0055] Example 3
[0056] S1. Dissolve 4.0 g FeCl3, 4.9 g MnCl2·4H2O and 10.0 g ZnCl2 completely in 30 mL pure water, add 10.0 g dregs powder, and stir thoroughly until a paste is formed to obtain the precursor;
[0057] S2. The precursor of S1 was placed in a tubular furnace, and under the protection of argon, the temperature was raised to 900°C at a rate of 5°C / min, and pyrolyzed at 900°C for 2 h. After cooling to room temperature, a zero-valent iron-manganese bionic coral island was obtained.
[0058] Comparative Example 1
[0059] This comparative example is a zero-valent iron bionic coral island (Fe@BC), and the specific preparation method is as follows:
[0060] S1. Dissolve 5.0 g FeCl3 and 10.0 g ZnCl2 completely in 30 mL pure water, add 10.0 g dregs powder, and stir thoroughly until a paste is formed to obtain the precursor;
[0061] S2. The precursor of S1 was placed in a tubular furnace, and under the protection of argon, the temperature was raised to 900°C at a rate of 5°C / min, and pyrolyzed at 900°C for 2 h. After cooling to room temperature, a zero-valent iron-manganese bionic coral island was obtained.
[0062] The only difference between this comparative example and Example 1 is that the manganese precursor MnCl2·4H2O is not added.
[0063] Comparative Example 2
[0064] This comparative example is a biochar-loaded manganese oxide nanoparticle (Mn@BC), and the preparation process is as follows:
[0065] S1. Dissolve 6.2 g MnCl2·4H2O and 10.0 g ZnCl2 completely in 30 mL pure water, add 10.0 g dregs powder, and stir thoroughly until a paste is formed to obtain the precursor;
[0066] S2. The precursor of S1 was placed in a tubular furnace, and under the protection of argon, the temperature was raised to 900°C at a rate of 5°C / min, and pyrolyzed at 900°C for 2 h. After cooling to room temperature, a zero-valent iron-manganese bionic coral island was obtained.
[0067] The only difference between this comparative example and Example 1 is that the iron precursor FeCl3 is not added.
[0068] Comparative Example 3
[0069] This comparative example is a zero-valent iron-manganese bionic coral island, and the preparation process is as follows:
[0070] S1. Dissolve 5.0 g FeCl3, 4.3 g MnCl2·4H2O and 10.0 g ZnCl2 completely in 30 mL pure water, add 10.0 g dregs powder, and stir thoroughly until paste-like to obtain the precursor;
[0071] S2. The precursor of S1 was placed in a tubular furnace, and under the protection of argon, the temperature was raised to 900°C at a rate of 5°C / min, and pyrolyzed at 900°C for 2 h. After cooling to room temperature, a zero-valent iron-manganese bionic coral island was obtained.
[0072] The difference from Example 1 is that the molar ratio of ferric chloride to manganese dichloride in the comparative example is 1:0.7, while the molar ratio of ferric chloride to manganese dichloride in Example 1 is 1:1.
[0073] Structural characterization:
[0074] Experimental materials: materials prepared in Example 1 and Comparative Examples 1-2.
[0075] Example 1: Zero-valent iron manganese bionic coral island prepared Figure 1 The XRD pattern of FeMn@BC is shown in Figure 1 As shown, a sharp graphite carbon peak appeared in FeMn@BC, and the characteristic peaks of zero-valent Fe and zero-valent Mn were detected at the same time. When only an iron precursor is added without a manganese precursor during the preparation process (the material of Comparative Example 1, marked as Fe@BC in the figure), zero-valent iron is mainly obtained, and the peak of graphite carbon is not obvious; when only a manganese precursor is added without an iron precursor during the preparation process (the material of Comparative Example 2, marked as Mn@BC in the figure), an obvious graphite carbon peak is observed, but no zero-valent manganese peak is observed. Manganese mainly exists in the form of MnO and Mn3O4, which also shows that under the carbon thermal reduction conditions, single manganese ions cannot be reduced to zero-valent manganese. The present invention has found that when iron and manganese ions coexist, zero-valent iron-manganese alloys can be prepared by a one-step carbon thermal method.
[0076] The final product prepared in Example 1 has a zero-valent iron manganese bionic coral island (FeMn@BC) as shown in the scanning electron microscope. Figure 2 As shown, from Figure 2 The electron microscope image on the left shows that the surface of the biochar is covered with regular and uniform zero-valent iron and manganese nanorods with a diameter of about 100 nm. Figure 2 On the right, we can see that the C, Fe, and Mn elements are distributed relatively evenly on the surface of the product, and the element distribution of C, Fe, and Mn is in the form of a nanorod array, which further shows that the zero-valent iron manganese nanorods are coated with a carbon film. Combined with the XRD diagram, it is a graphitized carbon film.
[0077] Effect Example 1
[0078] Experimental materials: zero-valent iron manganese bionic coral island (MnFe@BC) prepared in Example 1; zero-valent iron bionic coral island (Fe@BC) prepared in Comparative Example 1; biocarbon-loaded manganese oxide nanoparticles (Mn@BC) prepared in Comparative Example 2; zero-valent iron manganese bionic coral island prepared in Comparative Example 3.
[0079] Evaluation of Fenton-like catalytic degradation effect:
[0080] Experimental method: The simulated pollutant is selected as 2,4,6-trichlorophenol, but not limited to 2,4,6-trichlorophenol. 50.0 mL of wastewater (the wastewater contains 2,4,6-trichlorophenol at a concentration of 100.0 mg / L, and the natural pH of the wastewater is 5.0) and 0.02 g of the material prepared in Example 1, Comparative Example 1, Comparative Example 2 or Comparative Example 3 were added to a cylindrical glass reaction container, and 2.0 mL of 6% H2O2 solution was added without adjusting the pH. The reaction was started. After 2 h of reaction, a sample was taken, and the concentration of 2,4,6-trichlorophenol in the filtrate was immediately tested by HPLC after filtering with a 0.22 μm filter.
[0081] Experimental results: The results show that after adding the zero-valent iron manganese bionic coral island (FeMn@BC) prepared in Example 1 as a catalyst, the removal rate of 2,4,6-trichlorophenol reached 85.0%; after adding the zero-valent iron bionic coral island (Fe@BC) prepared in Comparative Example 1 as a catalyst, the removal rate of 2,4,6-trichlorophenol was only 48.8%; after adding the biochar-loaded manganese oxide nanoparticles (Mn@BC) prepared in Comparative Example 2 as a catalyst, the removal rate of 2,4,6-trichlorophenol was only 5.7%; after adding the zero-valent iron manganese bionic coral island prepared in Comparative Example 3 as a catalyst, the removal rate of 2,4,6-trichlorophenol was only 59.7%. Compared with the zero-valent iron manganese bionic coral island prepared in Example 1, the products prepared in Comparative Examples 1, 2 and 3 have significantly reduced pollutant removal capabilities.
[0082] The zero-valent iron-manganese bionic coral island obtained in Example 1 forms a zero-valent iron-manganese alloy. The zero-valent manganese has a standard reduction potential of -1.18V and has a stronger reduction ability than zero-valent iron. By forming an iron-manganese alloy, the reduction and dehalogenation ability of zero-valent iron is enhanced, and the dissolved Mn 2+ , Mn 3+ It not only has Fenton-like catalytic activity, but also can accelerate the Fe 3+ Fe 2+ The conversion efficiency is 2.3%. In the zero-valent iron manganese coral island, the zero-valent iron manganese bimetallic nanorod array wrapped with a layer of carbon film grows evenly on the porous biocarbon surface, shaped like a coral island. Just like corals prey on plankton, the iron manganese nanorods wrapped with a layer of carbon film can adsorb and capture hydrophobic halogenated organic pollutants in the water, thereby triggering the transfer of electrons from the zero-valent iron manganese to the captured halogenated organic pollutants to achieve reduction and dehalogenation. The graphitized carbon film can also promote the transmission of electrons in the degradation reaction of pollutants. In addition, the zero-valent iron manganese bionic coral island has excellent catalytic H2O2 performance, combined with reduction and dehalogenation and catalytic oxidation functions, so that its removal efficiency for chlorophenol compounds reaches 85.0%.
[0083] In Comparative Example 1, the reduction ability of the obtained zero-valent iron is not as good as that of the zero-valent iron-manganese alloy, and the degree of graphitization of the wrapped carbon film is also low, which is not conducive to the transfer of electrons in the reduction and oxidation reactions; in Comparative Example 2, although the degree of graphitization of the wrapped carbon film is high, zero-valent manganese is not obtained, and manganese mainly exists in the form of MnO and Mn3O4, and its reduction dehalogenation ability and Fenton catalytic activity are relatively low; in Comparative Example 3, although a zero-valent iron-manganese alloy is also obtained, the zero-valent manganese content is too low, and the degree of graphitization of carbon is not high enough, so its original dehalogenation ability and Fenton catalytic activity are relatively low.
[0084] Effect Example 2
[0085] Experimental materials: zero-valent iron manganese bionic coral island prepared in Example 2.
[0086] Evaluation of Fenton-like catalytic degradation effect:
[0087] Experimental method: The simulated pollutant is selected as 2,4,6-trichlorophenol, but not limited to 2,4,6-trichlorophenol. 50.0 mL of wastewater (the wastewater contains 2,4,6-trichlorophenol at a concentration of 100.0 mg / L, and the natural pH of the solution is 5.0) and 0.02 g of the zero-valent iron-manganese bionic coral island prepared in Example 2 were added to a cylindrical glass reaction container. Without adjusting the pH, 2.0 mL of 6% H2O2 solution was added to start the reaction. After 2 h of reaction, a sample was taken, filtered using a 0.22 μm filter, and the concentration of 2,4,6-trichlorophenol in the filtrate was immediately tested by HPLC.
[0088] Experimental results: The results show that after adding the zero-valent iron-manganese bionic coral island prepared in Example 2 as a catalyst, the removal rate of 2,4,6-trichlorophenol reached 83.6%, showing a high catalytic activity.
[0089] Effect Example 3
[0090] Experimental materials: zero-valent iron manganese bionic coral island prepared in Example 3.
[0091] Evaluation of Fenton-like catalytic degradation effect:
[0092] Experimental method: The simulated pollutant is selected as 2,4,6-trichlorophenol, but not limited to 2,4,6-trichlorophenol. 50.0 mL of wastewater (the wastewater contains 2,4,6-trichlorophenol at a concentration of 100.0 mg / L, and the natural pH of the solution is 5.0) and 0.02 g of the zero-valent iron-manganese bionic coral island prepared in Example 3 were added to a cylindrical glass reaction container. Without adjusting the pH, 2.0 mL of 6% H2O2 solution was added to start the reaction. After 2 h of reaction, a sample was taken, filtered using a 0.22 μm filter, and the concentration of 2,4,6-trichlorophenol in the filtrate was immediately tested by HPLC.
[0093] Experimental results: The results show that after adding the zero-valent iron manganese bionic coral island prepared in Example 3 as a catalyst, the removal rate of 2,4,6-trichlorophenol reached 85.9%, showing a high catalytic activity.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. For ordinary technicians in this field, other different forms of changes or modifications can be made based on the above descriptions and ideas. It is not necessary and impossible to list all the implementation methods here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a zero-valent iron-manganese bionic coral island, characterized in that: The following steps are involved: S1. Mixing zinc chloride, ferric chloride, manganese dichloride and biomass raw materials in water to obtain a precursor; S2. The precursor described in S1 is pyrolyzed at 870-950° C. under an inert atmosphere, and post-treated to obtain a zero-valent iron-manganese bionic coral island; Wherein, the molar ratio of ferric chloride to manganese dichloride is 1: (0.8-1.1); The mass ratio of the biomass raw material to zinc chloride is 1: (0.8-1.2); The mass ratio of the biomass raw material to ferric chloride is 1: (0.4-0.6) The zero-valent iron-manganese bionic coral island is a zero-valent iron-manganese alloy surface coated with a graphitized carbon film; the pyrolysis time is 1.5 to 3 hours.
2. The preparation method according to claim 1, characterized in that: The heating rate of the pyrolysis is 3-8 °C / min.
3. The preparation method according to claim 1, characterized in that: The biomass raw material is one or more of straw, wheat bran, rice husk, leaves or bean dregs.
4. The preparation method according to claim 1, characterized in that: The inert atmosphere is nitrogen or argon.
5. The zero-valent iron-manganese bionic coral island prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the zero-valent iron manganese bionic coral island described in claim 5 in degrading organic pollutants.
7. The use according to claim 6, characterized in that: The organic pollutants are halogenated organic pollutants.
Citation Information
Patent Citations
Nano zero-valent iron manganese bi-metal and preparation method and application thereof
CN111804930A
Remediation agent for water body and soil polluted by sulfonylurea herbicide as well as preparation method and application of remediation agent
CN116492981A
Preparation method of triple modified nano zero-valent iron composite material, material and application of material
CN118950022A